Operational Audit of Accounts Receivable (Study at PT. Sanserita Jaya) - Ahmad Winanto; Fika Aryani (Institut Ilmu Sosial dan Manajemen Stiami, 2020)
An operational audit of accounts receivable is needed because it plays a role in assessing the effectiveness of accounts receivable so that it runs according to established procedures and policies. This study aims to determine the role of operational audits on the functions of accounts receivable and to determine the function of accounts receivable in overcoming the accounts receivable turnover. The research was conducted at PT. Sanserita Jaya which is a company engaged in the distribution of raw materials and printing machinery. The method used in this research is descriptive research method. The focus in this research is the procedure for the function of the accounts receivable section. The results of the study explained that based on data analysis in 2017-2019, showed that the procedure of accounts receivable was quite effective but there were still many weaknesses found, based on these weaknesses the researchers submitted several recommendations for improvements so that the company could fix existing weaknesses and increase the effectiveness of managing its accounts receivable.